GENIPSO: a French prospective study assessing instantaneous prevalence, clinical features and impact on quality of life of genital psoriasis among patients consulting for psoriasis. (1st March 2019) - Larsabal, M.; Ly, S.; Sbidian, E.; Moyal‐Barracco, M.; Dauendorffer, J.‐N.; Dupin, N.; Richard, M.A.; Chosidow, O.; Beylot‐Barry, M.; Abdo, Ivana; Acquitter, Marie; de la Breteque Mignot, Maud Ami; et al.
Summary: Background: Genital psoriasis is often under‐recognized. Objectives: To assess the instantaneous prevalence of genital psoriasis and describe its clinical features, association with a particular subtype of psoriasis and its impact on general and sexual quality of life (QoL). Methods: GENIPSO is a prospective study conducted by private and hospital‐based dermatologists. This study featured the consecutive inclusion of patients consulting for extragenital psoriasis. The clinical features of psoriasis and genital psoriasis were recorded and QoL and sexual health questionnaires were distributed to patients. Results: Overall, 335 of 776 patients (43·2%) included in the study had genital involvement. All were aware that they had genital lesions but only 135 patients (40%) declared that they had been previously examined. Genital lesions were associated with male sex, severity of psoriasis, age of onset > 20 years, inverse psoriasis and involvement of scalp, nail and external auditory canal, but were not associated with obesity, psoriatic arthritis and active sex life. Itching was the main symptom. Genital psoriasis was associated with impairment of QoL and sexual health according to the Dermatology Life Quality Index and the Female Sexual Function Index. Conclusions: Genital psoriasis has a high prevalence in patients consulting for extragenital psoriasis, which affects QoL, and should be taken into account by dermatologists in order to optimize global care.